KEMAMPUAN PENERAPAN DIKSI PESERTA DIDIK KELAS V SD XAVERIUS 1 PALEMBANG - Uswatun Hasanah (Jurnal PGSD Musi, 2019)
This study aims to analyze the text produced by students in class V SD Xaverius 1 Palembang with the topic Banjir. This type of research uses a mix method that combines qualitative and quantitative approaches. The population in this study amounted to 110 students with a sample of 40 students. The writings of the students were assessed by the researcher and validated triangulation by one linguist. Based on the research that has been done, it can be concluded that the language assessment gets 0 as many as 25 students, 0.5 values as many as 11 students, and those who get a value of 1 are 4 students.